THE RISK-TAKING BEHAVIOUR OF INDONESIAN BANKS USING SCP PARADIGM - Nitha Pricillia (Center for Economic Studies Universitas Katolik Parahyangan, 2015)
Bank has the main function as an intermediation institution, whose role is transferring funds from those who has excess in it to those who need it. Banks also have an objective in maximizing profit. Therefore, the rules and executions of bank’s risk management are based on the balancing of maximization of profit and the minimization of risks that comes with this profit maximization activity. This paper is aiming at finding the factors that determine the risk-taking behaviour of Indonesian banks, using the Structure Conduct and Performance (SCP) paradigm. According to this paradigm, bank’s decision making (its conducts) is influenced by the dynamic of its structure, and the level of performance it wants to achieve. Also, these conducts or decisions reflect bank’s risk preference, or its risk-taking behaviour. Using 2 Stage Least Square regression method, this paper finds that there are seven factors that determine bank’s risk-taking behaviour in Indonesia. These factors are the Capital Adequacy Ratio (CAR) level, the amount of capital, the expectation on profit, the expectation on inefficiency, industry concentration ratio, the level of bank’s importance in Indonesia’s economy, and the movement of Bank Indonesia’s rate.Keywords: Banking risk, bank’s risk-taking behavior, banking risk management.